Infective Causes of Epilepsy - Bonello, M.; Michael, B.D.; Solomon, T. (Seminars in Neurology, 2015)
A wide range of infections of the central nervous system are responsible for both acute seizures and epilepsy. The pathogenesis and clinical semiology of the seizure disorders vary widely between the infective pathogens. The exact mechanisms underlying this are poorly understood, but appear, at least in part, to relate to the pathogen; the degree of cortical involvement; delays in treatment; and the host inflammatory response. The treatment of infective causes of seizures involves both symptomatic treatment with antiepileptic drugs and direct treatment of the underlying condition. In many cases, early treatment of the infection may affect the prognosis of the epilepsy syndrome. The greatest burden of acute and long-term infection-related seizures occurs in resource-poor settings, where both clinical and research facilities are often lacking to manage such patients adequately. Nevertheless, education programs may go a long way toward addressing the stigma, leading to improved diagnosis, management, and ultimately to better quality of life.
Keywords: infection; encephalitis; epilepsy